TITLE TRANSLATION : A CASE STUDY OF JAPANESE TRANSLATION OF BOLLYWOOD FILM TITLES (International Journal of Food and Nutritional Sciences, 2022)
Bollywood film industry is one of the largest film industries in terms of production in the world. Since Bollywood films are made in Hindi language, they are required to be dubbed or/and subtitled in foreign languages for their release in foreign countries. One of the important parts during this process is translation of the title. It is a crucial step because the title gives the first impression of a film. In this research paper, how the titles of Hindi films are translated in Japan, a country where Bollywood films are being released and relished for several decades now, has been discussed. A comparative analysis between the titles of Hindi films and their Japanese versions would be drawn. A total number of 18 film titles and their translations have been taken as a sample in this study. In order to examine these titles and how they have been translated, the method of content analysis has been applied.